Variability, petrography and provenance of basement clasts from CRP-2/2A drillcore (Victoria Land Basin, Antarctica) - TALARICO, F. M.; SANDRONI, S.; FIELDING, C.; ATKINS, C. (2000)
SciVal Topics Metrics Abstract Distribution patterns, petrography, whole-rock and mineral chemistry, and shape and fabric data are described for the most representative basement lithologies occurring as clasts (granule to boulder grain-size class) from the 625 m deep CRP-2/2A drillcore. A major change in the distribution pattern of the clast types occurs at c. 310 mbsf, with granitoid-dominated clasts above and mainly dolerite clasts below: moreover, compositional and modal data suggest a further division into seven main detrital assemblages or petrofacies. In spite of this variability, most granitoid pebbles consist of either pink or grey biotite±hornblende monzogranites. Other less common and ubiquitous lithologies include biotite syenogranite, biotite±hornblende granodiorite, tonalite, monzogranitic or monzonitic porphyries (very common below 310 mbsf), microgranite, and subordinately, monzogabbro, Ca-silicate rocks, biotite-clinozoisite schist and biotite orthogneiss (restricted to the pre-Pliocene strata). The ubiquitous occurrence of biotite±hornblende monzogranite pebbles in both the Quaternary-Pliocene and Miocene-Oligocene sections, apparently reflects the dominance of these lithologies in the onshore basement, and particularly in the Cambro-Ordovician Granite Harbour Igneous Complex which forms the most extensive outcrop in southern Victoria Land. The petrographical features of the other CRP-2/2A pebble lithologies are consistent with a supply dominantly from areas of the Transantarctic Mountains facing the CRP-2/2A site, and they thus provide further evidence of a local provenance for the supply of basement clasts to the CRP-2/2A sedimentary strata.